The use of sleep aids among Emergency Medicine residents: a web based survey - Raja Ali; Handel Daniel A; Lindsell Christopher J (BMC, 2006)
Abstract Background Sleepiness is a significant problem among residents due to chronic sleep deprivation. Recent studies have highlighted medical errors due to resident sleep deprivation. We hypothesized residents routinely use pharmacologic sleep aids to manage their sleep deprivation and reduce sleepiness. Methods A web-based survey of US allopathic Emergency Medicine (EM) residents was conducted during September 2004. All EM residency program directors were asked to invite their residents to participate. E-mail with reminders was used to solicit participation. Direct questions about use of alcohol and medications to facilitate sleep, and questions requesting details of sleep aids were included. Results Of 3,971 EM residents, 602 (16%) replied to the survey. Respondents were 71% male, 78% white, and mean (SD) age was 30 (4) years, which is similar to the entire EM resident population reported by the ACGME. There were 32% 1st year, 32% 2nd year, 28% 3rd year, and 8% 4th year residents. The Epworth Sleepiness Scale (ESS) showed 38% of residents were excessively sleepy (ESS 11-16) and 7% were severely sleepy (ESS>16). 46% (95 CI 42%-50%) regularly used alcohol, antihistamines, sleep adjuncts, benzodiazepines, or muscle relaxants to help them fall or stay asleep. Study limitations include low response and self-report. Conclusion Even with a low response rate, sleep aid use among EM residents may be common. How this affects performance, well-being, and health remains unknown.